The Transformation of Hermitages into Augustinian Priories in Twelfth-Century England - Herbert, Jane (Studies in church history, 1985)
The transformation of eremitic communities into Augustinian priories was a notable feature of early Augustinian growth; during the twelfth century no less than about 50 houses of the order began in this way. The popularity of the eremitic way of life had increased considerably during the eleventh century and, once established, a hermit often inspired others to join him, thus becoming the unwitting instigator of a religious group which needed formal organization. The Rule of St. Augustine was the constitution most frequently adopted in these circumstances. This was because it provided a general framework for community life rather than a set of detailed instructions and could therefore be assimilated more easily by an established group.